The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/smsc.202300093
|View full text |Cite
|
Sign up to set email alerts
|

Phase Engineering of Two‐Dimensional Transition Metal Dichalcogenides

Jong Hun Kim,
Hayeong Sung,
Gwan-Hyoung Lee

Abstract: Since the successful isolation of single‐layer graphene with an atomic thickness, various van der Waals (vdW) materials have been intensively studied owing to their unique properties. Among the families of vdW materials, transition metal dichalcogenides (TMDs) have served as representatives because of their diverse band structures and intriguing quantum states, unlike those observed in their bulk counterparts. Particularly, unconventional polymorphic phases of TMDs increase the degrees of freedom in device fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 665 publications
0
0
0
Order By: Relevance
“…It is found that the hexagonal phase is the most thermodynamically stable phase for WSe 2 . On the other hand, the orthorhombic phase is the most stable phase of WTe 2 , rather than the hexagonal one . Due to this difference, an intermediate state emerges at x = 0.5, where both the hexagonal (2H) and orthorhombic (Td) phases coexist in the material .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…It is found that the hexagonal phase is the most thermodynamically stable phase for WSe 2 . On the other hand, the orthorhombic phase is the most stable phase of WTe 2 , rather than the hexagonal one . Due to this difference, an intermediate state emerges at x = 0.5, where both the hexagonal (2H) and orthorhombic (Td) phases coexist in the material .…”
Section: Resultsmentioning
confidence: 96%
“…42 On the other hand, the orthorhombic phase is the most stable phase of WTe 2 , rather than the hexagonal one. 43 Due to this difference, an intermediate state emerges at x = 0.5, where both the hexagonal (2H) and orthorhombic (Td) phases coexist in the material. 26 In this study, we propose a layered material consisting of a superlattice formed by the combination of WSe 2 and WTe 2 .…”
Section: ■ Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…4−6 Phase-engineering in many ways is a deeply convoluted engineering tool for TMDs, as it is synergistically correlated and induced by many other engineering strategies or vice versa, such as intercalation/exfoliation, defects, thermochemical treatments, strain engineering, and structural distortions. 49,360 With exfoliation and intercalation by alkali ions, organic ligands have led to 2H-to-1T phase transformations in TMDs. Detailed studies on exfoliations of TMDs (MoS 2 , MoSe 2 , WS 2 , and WSe 2 ) using aromatic intercalants such as phenyllithium, sodium naphthalenide, and sodium anthracenide elucidated the intercalation effects on electrochemical HER performance, with PhLi-intercalated MoS 2 showing the best performance due to its high edge density and exposure of metal-ion sites.…”
Section: Initial Studies and Basis For Engineering Tmdsmentioning
confidence: 99%
“…Different phase structures lead to huge disparity in the properties of the TMDC nanomaterials [ 21 , 22 , 23 , 24 , 25 ]. For example, molybdenum disulfide (MoS 2 ) exhibits all three phase structures.…”
Section: Introductionmentioning
confidence: 99%